Nutritional status and body composition of juvenile elite female gymnasts - Filaire, E.; Lac, G. F. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The purpose of this study was to examine body composition, dietary intake and energy expenditure in 12 young female elite gymnasts aged 10.1[plus minus]0.3 years, doing a physical exercise of 15 hrs x week-1. The results were compared with a control group consisting of nine volunteer school girls age matched doing less than 4 hrs x wk-1 of physical exercise. METHODS: Assessments included dietary intake for 7 days, anthropometric measurements (body weight, height, arm circumference, triceps and subscapular skinfolds, body mass index). Body fat percentage was estimated using the Slaughter equation. Anthropometric measurements and nutritional intake were recorded in autumn. RESULTS: The gymnasts were shorter and had lower body weight compared with controls (p<0.05). Percentage of body fat was significantly lower in gymnasts versus controls (p<0.01). Gymnasts had higher percentage of fat free mass (p<0.01) than the reference group. Daily energy intake met daily energy requirement in both groups. Distribution of energy for both groups was almost identical, with approximately 14% from protein, 48% from carbohydrate, and 37% from fat. The average intakes of polyunsaturated fat were low in the two groups. The main daily intake of most nutrients in both groups were in accordance with recommendations; exceptions were dietary fibre, E and B6 vitamins. CONCLUSIONS: The primary finding of this investigation is that in both groups, the mean daily energy intake met the energy requirement. Thus, the gymnasts did not restrict total energy. The overall nutrient intake of the two groups may appear adequate. Prepubertal gymnasts have higher percentage of fat free mass and daily energy expenditure and dietary intakes, but lower percent body fat than age matched controls.